Stimulation of locus coeruleus increases arterial pressure in rabbits - Chen Yong-Yue; Huang Zhong-Sun (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of electric and chemical stimulation of locus coeruleus (LC) on arterial pressure and renal sympathetic nerve discharge activity (RSA). METHODS: Electric stimulation of LC and microinjection of L-glutamate (L-Glu), morphine, and GABA into the LC of rabbits were made. The LC was destructed electrolytically. Arterial pressure and RSA were recorded. RESULTS: Both electric stimulation (150 microA, 50 Hz) of the LC and microinjection of L-Glu (0.5 mumol) into unilateral LC elicited increases in arterial pressure (13.5 +/- 0.3 vs 19.5 +/- 0.8 kPa, P < 0.01 and 13.8 +/- 0.4 vs 17.5 +/- 0.8 kPa, P < 0.01, respectively) and RSA (by 107 +/- 14%, P < 0.01, and 88 +/- 21%, P < 0.01, respectively). Microinjection of morphine or GABA did not induce any significant changes in the above two parameters. Electrolytic lesion of the LC eliminated the pressor response induced by microinjection of L-Glu. CONCLUSION: Excitation of LC has a pressor effect in rabbits, but LC is not a crucial nucleus in tonic regulation of blood pressure.